The intertemporal connection between preschool delay of gratification and later academic performance in primary schools: Evidence from China - Zheng Li (Journal of Applied Economics, 2022)
A child's ability to resist temptation is an important non-cognitive skill and associated with lifetime benefits. Using a longitudinal dataset, this study links Chinese preschoolers' delay of gratification to their later scholastic performance during primary education. An empirical investigation is conducted to explore the potential relation between them. The results show that this personality trait, revealed at age 4-5 years by using the marshmallow experiment, has a long-lasting and positive contribution, even after accounting for students' cognitive performance and other non-cognitive skills measured at age 10-11 years. Our findings in a developing country context are supported by evidence from developed countries.
Keywords: 330; Delay of gratification; non-cognitive skills; ordered logit; schooling performance